Land Governance in South Sudan : Policies for Peace and Development - World Bank (Washington, DC, 2014)
South Sudan is a new country of 10.5 million people that has just emerged from conflict and still facing challenges with recovery and development. Although economic disparities, political exclusion and deprivation in the distribution of political and economic power between the northern and southern parts of then united Sudan were often tendered as the proximal causes of the conflict, at the center of the prolonged civil war was the struggle for ownership, control and use of land resources. The tool underpinning this report is the Land Governance Assessment Framework (LGAF), a diagnostic instrument for rapid evaluation of various aspects of land governance. LGAF was developed through a collaborative effort between the World Bank, Food and Agriculture Organization (FAO), UN Habitat, International Fund for Agriculture Development (IFAD), the International Food Policy Research Institute (IFPRI) and the African Union (AU).